Enhanced wear and corrosion in modular tapers in total hip replacement is associated with the contact area and surface topography. Issue 12 (21st August 2013) - Panagiotidou, Anna; Meswania, Jay; Hua, Jia; Muirhead‐Allwood, Sarah; Hart, Alister; Blunn, Gordon
ABSTRACT: Widespread concern exists about adverse tissue reactions after metal‐on‐metal (MoM) total hip replacement (THR). Concerns have also been expressed with wear and corrosion of taper junctions in THR. We report the effect of surface finish and contact area associated with a single combination of materials of modular tapers. In an in vitro test, we investigated the head/neck (CoCrMo/Ti) interface of modular THRs using commercially available heads. Wear and corrosion of taper surfaces was compared following a 10 million loading cycle. Surface parameters and profiles were measured before and after testing. Electrochemical static and dynamic corrosion tests were performed under loaded and non‐loaded conditions. After the load test, the surface roughness parameters on the head taper were significantly increased where the head/neck contact area was reduced. Similarly, the surface roughness parameters on the head taper were significantly increased where rough neck tapers were used. Corrosion testing showed breaching of the passive film on the rough but not the smooth neck tapers. Thus, surface area and surface finish are important factors in wear and corrosion at modular interfaces. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:2032–2039, 2013